Land of the Pilgrims' pride - Gingrich, Callista; Arciero, Susan (Washington, DC : Regnery Kids, an imprint of Regnery Publishing, Inc., 2012)
Ellis the Elephant explores the story of America's beginnings as he learns about each of the original 13 colonies.
Ages 4-8.
Keywords: Elephants -- Juvenile fiction; Elephants -- Fiction; United States -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature; Picture books for children